Hubungan Konsep Diri dengan Perilaku Asertif Siswa - Rukmana, Dela Dwi; Zikra, Zikra (ALSYS, 2024)
This research was motivated by the low level of assertive behavior of students at SMP Negeri 13 Padang. Many factors influence assertive behavior, one of which is self-concept. The self-concept of students at SMP Negeri 13 Padang also experiences problems. Further research was conducted regarding the relationship between self-concept and assertive behavior of students at SMP Negeri 13 Padang. The aims of this research are: (1) to describe students' self-concept; (2) describe students' assertive behavior; (3) examine the relationship between self-concept and assertive behavior of students at SMP Negeri 13 Padang. This research uses quantitative methods with a descriptive approach. The sample in this study was 245 students at SMP Negeri 13 Padang who were selected using a stratified random sampling technique. Data was obtained using self-concept and assertive behavior questionnaires which were valid and reliable. Data processing is carried out using the product moment correlation formula. The results of the research show that the self-concept of students at SMP Negeri 13 Padang is in the sufficient category (63.27%), the assertive behavior of students at SMP Negeri 13 Padang is in the sufficient category (51.02%) and there is a significant relationship between self-concept and assertive behavior with a coefficient (0.447).